The limits of American labor‘s influence on the cold war free labor movement: a case study of Irving Brown and the International Confederation of Free Trade Unions in Tunisia and Algeria - Fitzloff, Chad L. (Kansas State University, 2010)
In 1988, Irving Brown received the Medal of Freedom from President Ronald Reagan for playing a crucial role in breaking the hold of international communism over postwar Western Europe. By doing so, he can truly be called one of the architects of Western democracy. Brown also made extraordinary efforts to fight international Communism in French North Africa during the 1950s. This paper seeks to answer the question of why these efforts in North Africa failed, and it will show the limits of American labor‘s international influence during the Cold War, in particular in French North Africa. Irving Brown successfully strengthened anti-Communist unions in Europe, and had the financial backing of the Truman Administration for those projects. However, Brown‘s efforts to build anti-Communist trade unions in Tunisia and Algeria did not have the backing of the U.S. government under the Eisenhower Administration. Instead, the AFL-CIO, with Brown as its representative, attempted to use the non-Communist International Confederation of Free Trade Unions (ICFTU) to influence the nationalist movements of Tunisia and Algeria through their respective national unions, the Union générale tunisienne du travail (UGTT) and the Union générale des travailleurs algériens (UGTA). Disagreements within the ICFTU severely inhibited Brown‘s effectiveness and prevented him from fully realizing the AFL-CIO‘s policy goals in North Africa. Brown was overly dependent on Tunisia for his operations with the Algeria labor movement, and the ICFTU was incapable of providing adequate support to the Algerians to compete with its Communist rival, the World Federation of Trade Unions. To the extent that independent Tunisia was Western-oriented, Brown was successful in his efforts. However, in the long run, Brown failed as an architect of Western democracy, as Tunisia became a dictatorship with a socialist economy. In Algeria, the state of war forced the UGTA to turn to the Eastern bloc despite Brown‘s personal dedication to North African independence and development. Furthermore, in independence, Algeria‘s government embraced socialism and single party rule.
Keywords: United States labor; Algeria labor; Tunisia labor; Cold War; Irving Brown; International Labor; Economics, Labor (0510); History, African (0331); Political Science, International Law and Relations (0616)